Analisis Efektivitas Kebijakan Penghapusan Sanksi Administrasi Pajak Bum Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) Dalam Upaya Meningkatkan Penerimaan Pajak Daerah Kota Bekasi Tahun 2023 - Harjo, Dwikora; Wirabuana, Prayoga Indra (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Regional Tax is a tax collected and managed by the local government to finance all functions of government and development of the region. The Regional Revenue Agency is a regional apparatus whose function is to manage all types of revenue and income from regional assets, one of them is the Rural and Urban Land and Building Tax (PBB- P2). The aim of this research was to find out the effectiveness of the Policy for Eliminating Administrative Sanctions for Rural and Urban Land and Building Taxes (PBB-P2) in an effort to increase Regional Tax Revenue of Bekasi City, as well as the obstacles and efforts made in this policy. This research used descriptive qualitative research methods. Data collection from this research was by interviews, observation, and documentation. The theory used in this research is Effectiveness according to Duncan in Richard M. Steers (2020:53). The results of this research showed that the effectiveness of the policy to eliminate PBB-P2 administrative sanctions in Bekasi City was considered less effective, this means that the PBB-P2 revenue target for 2023 had not been achieved. This policy was less than optimal due to several obstacles such as a lack of taxpayer awareness, socialization inequality, and a lack of officers in socializing this policy. Efforts that could be made by the Bekasi City Regional Revenue Agency were to carry out regular socialization by collaborating with districts, sub-districts, and RT/RW (Neighborhood Unit/Community Unit).